Sweat gland density and response during high-intensity exercise in athletes with spinal cord injuries - Pritchett, RC; Al-Nawaiseh, AM; Pritchett, KK; Nethery, V; Bishop, PA; Green, JM (Biology of Sport, 2015)
Sweat production is crucial for thermoregulation. However, sweating can be problematic for individuals with spinal cord injuries (SCI), as they display a blunting of sudomotor and vasomotor responses below the level of the injury. Sweat gland density and eccrine gland metabolism in SCI are not well understood. Consequently, this study examined sweat lactate (S-LA) (reflective of sweat gland metabolism), active sweat gland density (SGD), and sweat output per gland (S/G) in 7 SCI athletes and 8 able-bodied (AB) controls matched for arm ergometry VO2peak. A sweat collection device was positioned on the upper scapular and medial calf of each subject just prior to the beginning of the trial, with iodine sweat gland density patches positioned on the upper scapular and medial calf. Participants were tested on a ramp protocol (7 min per stage, 20 W increase per stage) in a common exercise environment (21±1°C, 45-65% relative humidity). An independent t-test revealed lower (p<0.05) SGD (upper scapular) for SCI (22.3 ±14.8 glands · cm-2) vs. AB. (41.0 ± 8.1 glands · cm-2). However, there was no significant difference for S/G between groups. S-LA was significantly greater (p<0.05) during the second exercise stage for SCI (11.5±10.9 mmol · l-1) vs. AB (26.8±11.07 mmol · l-1). These findings suggest that SCI athletes had less active sweat glands compared to the AB group, but the sweat response was similar (SLA, S/G) between AB and SCI athletes. The results suggest similar interglandular metabolic activity irrespective of overall sweat rate.